Marketing of sea bass and sea bream in France - Riera P.; Lensi P. (Marketing of aquaculture products, 1996)
This text deals with the marketing of sea-bass and more particularly focuses on one of the most strategic keys of success in the field: the critical size of the companies.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/10/11-13, Thessaloniki (Greece)